Implementation Of Halal Lifestyle For Students In Choosing Cosmetics At Al-Amien Prenduan Idia Putri Islamic Boarding School - Nuri Safitrih; Lailatul Qadariyah; Sarkawi . (JOURNAL OF SHARIA ECONOMICS, 2023)
Halal lifestyle is an obligation for every Muslim who has faith. It's not enough just to say it, but as Muslims we have to implement Islam in our lives in a big way. Islamic boarding school is a place of education that teaches religious knowledge through books that are adapted to the curriculum according to the final expectations of the students' output . In Islamic boarding schools, many of the students are already teenagers with different thought patterns and lifestyles, such as maintaining their appearance by using cosmetics. The choices vary by considering price, suitability for the skin or perhaps recommendations from friends. Therefore, the aim of this research is to find out the halal lifestyle of Al-Amien Prenduan Islamic Boarding School students in choosing cosmetics and to find out what types of cosmetic products are often chosen by Al-Amien Prenduan Islamic Boarding School students. This research was conducted using qualitative methods using exploratory methods , the data collection techniques used were observation and interviews. And the results of interviews with resource persons regarding the implementation of a halal lifestyle in choosing cosmetic products can be concluded that Mahasantri Al-Amien Prenduan Idia Putri has implemented a halal lifestyle in choosing cosmetic products